Mengurai Gagasan Tan Malaka dari Perspektif Kajian Pendidikan Kewarganegaraan - R. Samidi; Suharno Suharno (Department of History, Faculty of Humanities, Diponegoro University, 2019)
This study identifies Tan Malaka's ideas in the perspective of Civic Education by exploring his great idea of Gerpolek which had published in a book. The published book supported by several other works, then analyzed in the context of Citizenship Education. Based on the results of the study shows that each of Tan Malaka's revolutionary ideas from the perspective of Citizenship Education has real contribution in the relation to build citizenship and the state, whether it seen from the context of nationalism, economics, politics, and human rights. Through Citizenship Education, it is appropriate that Tan Malaka placed in line with the national founders. His work becomes a reference in order to build the nation for the better future.